Effect of deficit irrigation and nitrogen levels on water productivity and nitrogen use efficiency of wheat (Triticum aestivum) in a semi-arid environment - PRADHAN, S; CHOPRA, U K; BANDYOPADHAYAY, K K; SINGH, R; JAIN, A K; CHAND, I (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out during 2009-10 and 2010-11 on a sandy loam soil of IARI, New Delhi on wheat (Triticum aestivum L.) with four levels of irrigation (rainfed, irrigations to replenish 30, 60 and 100% moisture deficit from field capacity) as main plot factors and four levels of nitrogen (0, 30, 60 and 120 kg N/ha) as subplot factors in a split plot design. The soil moisture storage in the profile showed inverse relation with the nitrogen levels whereas direct relationship was observed with the irrigation levels. The water use vs. wheat yield relation was linear and significant. Regression analysis showed that 58% variation in grain yield of wheat could be explained by water use. The grain yield showed increasing trend with increase in irrigation and nitrogen levels. The WP and EWP increased with increase in irrigation level up to 60% SMD and thereafter it decreased. However, both WP and EWP showed increasing trend with increase in nitrogen levels. The ANUE and PFPN increased with increase in irrigation levels, but with increase in nitrogen levels both ANUE and PFPN decreased. Grain yield, water productivity and nitrogen use efficiency showed significant interaction effect of irrigation and nitrogen.